Encyclopedia of marine mammals - Perrin, William F.; Wursig, Bernd G.; Thewissen, J. G. M.; Gale Group (San Diego, Calif. Academic Press, 2002)
Includes articles devoted to wide range of topics -- from the specific behavior and physiology of cetaceans and pinnipeds, to ecology, population biology, human effects and interaction, and research methodology.
Electronic reproduction.
Keywords: Marine mammals -- Encyclopedias; Electronic books